The Medical Liability Environment in San Juan: Results of a Survey - Cruz, Norma I. (Puerto Rico Health Sciences Journal, 2010)
Background: A survey was conducted to evaluate the effect that the current medical liability environment has had on physicians in San Juan, Puerto Rico. Methods: In August 2008 a questionnaire consisting of 15 items which evaluated medical liability was mailed to all physicians in the San Juan District. The questionnaire requested information on basic demographics, medical specialty, insurance coverage, changes made in medical practice to decrease medical liability risk, malpractice claims received during the last ten years, and whether awards exceeding insurance coverage were paid. Physicians were requested to return the completed questionnaires by FAX or mail. Results: There were 951 completed questionnaires returned. The survey indicated that 70% of physicians have made changes in their medical practices to decrease medical liability risk. Currently, 48% of physicians do not accept emergency cases and 50% do not accept high risk patients. Malpractice claims were received at least once in the previous ten years by 40% of the physicians. The awards requested by these claims exceeded the insurance coverage 75% of the time. After the final court decision was reached, 20% of the payments exceeded physicians’ insurance coverage. Conclusions: The adverse medical liability environment has affected the majority of physicians in San Juan, leading 70% of them to make changes in their practices to decrease the liability risk. As a result of these changes, the number of physicians willing to care for high risk and emergency patients has decreased significantly. [P R Health Sci J 2010;1:66-69]